Genetics of steroid‐resistant nephrotic syndrome: a review of mutation spectrum and suggested approach for genetic testing. (10th July 2013) - Joshi, S; Andersen, R; Jespersen, B; Rittig, S
Abstract: Identification of genes, associated mutations and genotype–phenotype correlations in steroid‐resistant nephrotic syndrome (SRNS) is being translated to clinical practice through genetic testing. This review provides an update on the genes and mutations associated with SRNS along with a suggested approach for genetic testing in patients with SRNS. Conclusion: The number of indentified genes associated with SRNS is increasing along with our understanding of their impact on treatment response and risk of recurrence. A systematic approach to genetic testing in patients with SRNS might aid the physician in selecting appropriate treatment.